Subscription of various health insurance schemes and factors influencing them in rural area of central Karnataka: a cross sectional study - G., Netra; Rao, B. A. Varadaraja (International Journal Of Community Medicine And Public Health, 2020)
Background: In a health insurance program, people who have the risk of a certain event contribute a small amount (premium) toward a health insurance fund. This fund is then used to treat patients who experience that particular event (e.g., hospitalization). It is a form of risk management which is used primarily to hedge against the risk of a contingent, uncertain loss. Health is wealth. Therefore, the concept of health insurance (HI) has evolved which finances health care. Objectives of the study was to assess subscription of various health insurance schemes and factors influencing them in the rural field practice area of SSIMS and RC, Davanagere. Methods: The cross sectional study was conducted in the rural field practice area of SSIMS and RC, Davangere from May to July 2016. A sample of 600 families were visited by systematic random sampling and data was collected from the head of the family with informed consent using a predesigned, pretested questionnaire by house to house interview. Analysis was done by using SPSS v10 and were results presented as percentages and proportions. Results: The total subscription in the study was 69.3%, Yeshasvini co-operative farmers’ health scheme coverage was 84% followed by others. The factors determining the subscription were the amount of premium, lack of funds, lack of awareness, lack of comprehensive coverage, etc. Conclusions: The premium has to be customized so that all the patients are benefited irrespective of the type of HI.